The routes for embolization of dural carotid cavernous fistulas when the endovascular approach is indicated as a first-line strategy - de Castro-Afonso, Luís Henrique (Interv Neuroradiol, 2018)
INTRODUCTION: Multiple ways to access the dural carotid cavernous fistula have been described. The aim of the present study was to assess the results of embolization of a dural carotid cavernous fistula via different routes using endovascular accesses as a first-line strategy. METHODS: A retrospective data analysis of a consecutive series of 63 patients presenting with dural carotid cavernous fistula was performed. RESULTS: The dural carotid cavernous fistula was accessed by an endovascular approach in 58 patients (92.1%) and by direct puncture in five patients (7.9%). The inferior petrosal sinus was the main route accessed (65%). A recanalization of an occluded inferior petrosal sinus was obtained in 20.6% of cases. The access via either facial ophthalmic veins or the superior petrosal sinus was obtained in 20.6% and 3.1% of cases, respectively. Complete angiographic occlusion of a dural carotid cavernous fistula immediately after treatment was achieved in 53 patients (84.1%), whereas 10 patients (15.9%) displayed a partial occlusion. Treatment-related complications were observed in two patients (3.2%). CONCLUSIONS: In this study, the endovascular approach allowed dural carotid cavernous fistula embolization in most patients. The inferior petrosal sinus, even when thrombosed, was the main route used to access the dural carotid cavernous fistula, followed by the facial vein, direct cavernous sinus puncture, and the superior petrosal sinus.